Model-Informed Precision Dosing - Pérez-Blanco, Jonás Samuel; Lanao, José Martínez (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Model-informed precision dosing (MIPD) is an advanced quantitative approach focusing on individualized treatment optimization. MIPD integrates mathematical models of drugs and diseases combined with individual patient characteristics (e.g., genotype, anthropometric factors, and organ function). MIPD has been highlighted as a useful tool for drug dosage selection in both the drug development process and clinical practice and it is a rapidly growing discipline that is supported by the main drug regulatory agencies. Despite the potential benefits of this methodology toward personalized medicine, its application is still limited. The Special Issue presented here includes several PKPD and PBPK models focused on improving the current state of art regarding the PK behaviour of different drugs with the aim of improving the efficacy/safety balance of these treatments and their clinical outcome; the Special Issue is intended to be of particular interest for clinical pharmacologists, pharmacometricians, and specific clinicians who routinely use the considered drugs.